Hubungan Antara Dukungan Sosial dengan Kecemasan Penderita Covid-19 dalam Menjalani Isolasi Mandiri di Kecamatan Karanganyar - Etik Surya Ariyani; Dewi Wulandari; Nurul Gilang Abriani (Indonesian Journal on Medical Science, 2022)
Social support into a thing that plays an important role for people that are convicted of a positive COVID-19. Anxiety is one of the psychosocial problems experienced by people who tested positive for COVID-19. This Study was to determine the relationship between social support with anxiety patients with covid-19 in undergoing the isolation of the self. A cross-sectional study. The population in this study were patients with covid-19 who underwent isolation of the self in Kecamatan Karanganyar, with a total sample of 74. Analysis of data using univariate Analysis with frequency distribution and bivariate tests provided by kendall's Tau-C. The analysis of research results showed that most respondents get high social support (70.7%) and experiencing mild anxiety (61.3%). There is a significant relationship between social support with anxiety patients with covid-19 in undergoing the isolation of the self in the district of Karanganyar.